(untitled) (Global Journal of Human-Social Science, 2012)
The study assessed the health risks associated with street trading activities among selected mothers in urban centers of Nigeria The data used was extracted from national survey data among 3 873 street traders selected in various Central Business Districts CBDs across three major cities of Nigeria namely Lagos Kano and Port Harcourt The study showed that street trading has provided job opportunities for mothers but the impact of the business on their welfare is not visible considering their weekly income that is far below their weekly expenditure Respondents with primary secondary and tertiary education are 0 879 0 553 and 0 818 less likely to be injured while trading on the street compared to individuals who have no formal education The authors suggest due recognition to be given to the activity and that street traders-government partnership be established in order to safeguard the health of the operators